Acyclovir Suppression to Prevent Recurrent Genital Herpes at Delivery - L. L. Scott; L. M. Hollier; D. McIntire; P. J. Sanchez; G. L. Jackson; G. D. Wendel (Hindawi Limited, 2002)
Objective: To determine if suppressive acyclovir near term decreased the frequency of clinical recurrences at delivery in women with recurrent genital herpes simplex virus (HSV) infection.